2015
DOI: 10.1073/pnas.1520760112
|View full text |Cite
|
Sign up to set email alerts
|

Human cerebral organoids recapitulate gene expression programs of fetal neocortex development

Abstract: Cerebral organoids-3D cultures of human cerebral tissue derived from pluripotent stem cells-have emerged as models of human cortical development. However, the extent to which in vitro organoid systems recapitulate neural progenitor cell proliferation and neuronal differentiation programs observed in vivo remains unclear.Here we use single-cell RNA sequencing (scRNA-seq) to dissect and compare cell composition and progenitor-to-neuron lineage relationships in human cerebral organoids and fetal neocortex. Covari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
855
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 953 publications
(925 citation statements)
references
References 39 publications
26
855
1
1
Order By: Relevance
“…Previously it was shown that high‐density NSC cultures spontaneously form neural aggregates that recapitulate several NSC niche components 37. In line with this, large neural aggregates or neural organoids exhibiting CNS tissue architecture have recently been described 38, 39. It has also been proposed that MICs could offer further benefits for culturing NSCs and NSC‐derived cells.…”
Section: Introductionmentioning
confidence: 84%
“…Previously it was shown that high‐density NSC cultures spontaneously form neural aggregates that recapitulate several NSC niche components 37. In line with this, large neural aggregates or neural organoids exhibiting CNS tissue architecture have recently been described 38, 39. It has also been proposed that MICs could offer further benefits for culturing NSCs and NSC‐derived cells.…”
Section: Introductionmentioning
confidence: 84%
“…Current brain organoids closely resemble fetal brains,28, 30, 66 and can only partially represent the diverse functional cell types of the brain, making them less ideal for studying complex network activities and circuit formations. It also raises the question as in to what extent can brain organoids effectively model neuropsychiatric or neurodegenerative diseases.…”
Section: Current Limitations Of Brain Organoidsmentioning
confidence: 99%
“…This human specific control could be due to genetic mutation in the human lineage (7) as illustrated by the gene Arhgap11b arisen from a duplication specific to the human lineage and involved in cortical expansion (3). This cell-autonomous control of precursor dynamics could also be due to specific regulation of gene expression [lnRNA (50,51); miRNA (52); different timings of gene expression (1,6,53)]. …”
Section: Heterochrony Is Cell Autonomousmentioning
confidence: 99%
“…Despite a wealth of recent influential studies addressing the specific features of the human gene regulatory network of corticogenesis (1)(2)(3)(4)(5)(6)(7), the question of what makes us human is still unresolved. The human cerebral cortex has achieved a unique degree of complexity considered to underlie the emergence of unrivaled cognitive abilities compared to other species including non-human primates (8,9).…”
Section: Introductionmentioning
confidence: 99%